Distributed control of interconnected Chemical Reaction Networks with delay. (November 2018) - Márton, Lőrinc; Szederkényi, Gábor; Hangos, Katalin M.
Highlights: A control-oriented modeling approach is proposed for interconnected CRNs (Chemical Reaction Networks), relying both on compartmental systems, and CRN theory. A distributed setpoint control algorithm is introduced which assures that the concentration levels of the chemicals in each CRN in the interconnected system reach prescribed fixed points. The proposed control algorithm is independent of the CRNs kinetics and the delay in the convection network. An extended version of the control algorithm is also introduced which is able to attenuate the effect of unknown input disturbances on the control performance. Abstract: This paper introduces a control approach for a class of Chemical Reaction Networks (CRNs) that are interconnected through a delayed convection network. First, a control-oriented model is proposed for interconnected CRNs. Second, based on this model, a distributed control method is introduced which assures that each CRN can be driven into a desired fixed point (setpoint) independently of the delay in the convection network. The proposed algorithm is also augmented with a disturbance attenuation term to compensate the effect of unknown input disturbances on setpoint tracking performance. The control design applies the theory of passive systems and methods developed for multi-agent systems. Simulation results are provided to show the applicability of the proposed control method.